Consumer behavior : building marketing strategy - Mothersbaugh, David L.; Kleiser, Susan Bardi; Hawkins, Del I. (New York: McGrawHill, 2024)
"Marketing attempts to influence the way consumers behave. These attempts have implications for the organizations making them, the consumers they are trying to influence, and the society in which these attempts occur. We are all consumers, and we are all members of society, so consumer behavior, and attempts to influence it, is critical to all of us. This text is designed to provide an understanding of consumer behavior. This understanding can make us better consumers, better marketers, and better citizens"--
Revised edition of the authors' Consumer behavior, [2020]
Includes index.
Keywords: Consumer behavior -- United States; Market surveys -- United States; Consumer behavior -- United States -- Case studies